Investigation of Effect of STAT5A Gene on Milk Yield and Composition in Jersey Cows - Soner Çankaya; Mehmet Ülker; Özden Çobanoğlu; Eser Kemal Gürcan; Ertuğrul Kul; Samet Hasan Abacı (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effect of STAT5A gene was investigated on milk yield and components (fat, protein) in Jersey cows. Because, this gene is a member of the signal transducers and activators of transcription the factor (STAT) family and thought to be the impact on milk yield and components. As a material in the research, 100 Jersey cows raised in Samsun Karakoy State Farm were used. Milk samples were collected 12 times with one month intervals after calving, and these samples were performed by ultrasonic milk analyzer for milk fat and protein content. In addition, test day milk yield (TDMY) of each cow were also recorded in the control days. C/G polymorphism with PCR-RFLP method result in DNA isolation from blood samples taken from cows was determined at 8.exon at position 12195. Genotype distribution was detected as 69% CC, 28% CG and 3% GG. Allele frequencies were found as 0.83 for the C allele and 0.17 for G allele. As a result of the polymorphism identified in STAT5A gene, statistically no difference were detected among genotypes for TDMY, 305 day milk yield (305 DMY), milk fat and protein rates and milk fat and protein yield. As a result, no significant differences were found between the milk yield and compositions association with STAT5A